Effects of short-term microbial fermentation of industrial potato waste on chemical contents and ruminal in vitro fermentation characteristics - Muhammad, Surajo Afaka (2023)
Potato processing generates waste in the form of peels, pulp and rejects which is estimated to be around 12-20% of their total production volume. Potato peels, pulp and unmarketable potatoes can further be processed in starch plants, incorporated into animal feed formulations, or turned into ethanol. However, there is limited nutritional information on the potential of industrial potato waste (IPW) as ruminant feed. Thus, this research aimed to validate and characterize experimental isolates, determine chemical composition and nutritive values of inoculated and fermented IPW, determine antinutritional factors (ANF), glycoalkaloid (GLA), and antioxidant capacity, and finally determine in vitro digestibility, microbial population, and rumen fermentation characteristics to up-cycle the industrial potato waste which will provide additional feed options for the livestock and make potato growing and processing more economical. The research design involved uninoculated IPW (control) and IPW inoculated with Lactiplantibacillus plantarum, Saccharomyces cerevisiae, and Aspergillus oryzae; thus each inoculated IPW served as a treatment. The treatments were subjected to fermentation at 0 (control), 24, 48, and 72 h. The layout of the experiment was a completely randomized (4 × 4) design (CRD) with factorial arrangement. In the first study, three isolates used for inoculation of IPW were characterized and confirmed as L. plantarum, S. cerevisiae, and A. oryzae with discrete accession numbers of MW296876, MW296931, and MW297015, respectively. The control, L. plantarum and S. cerevisiae treatments recorded gross energy (15.59 – 15.87 MJ/kg DM) higher (p<0.05) than 15.42 – 15.61 MJ/kg DM recorded for A. oryzae treatment. It was discovered that antioxidant capacity increased (33.94 – 41.39 Trolox Eq. mg/g) significantly (p<0.05) across the fermentation time (h) until 48 h; thereafter the antioxidant capacity dropped (27.02 – 35.94 Trolox Eq. mg/g). In the final study, treatment and fermentation time had no effect (p>0.05) on in vitro dry matter digestibility (IVDMD), in vitro organic matter digestibility (IVOMD), and metabolizable energy (ME). Although the methane content (7.11±1.49 – 8.07±0.32 mM) of A. oryzae did not changed across the fermentation time, the values recorded therein were significantly p<0.05) the lowest compared to other treatments with a range of 7.77 – 13.03 mM. Results on biohydrogenation revealed that IPW fermented with A. oryzae recorded significantly (p<0.05) highest concentration (1299.40 - 2085.29 μg/100 mL) of C18:0 (stearic acid) across all the fermentation time compared to 370.62 - 651.93 μg/100 mL recorded in the control, L. plantarum and S. cerevisiae. Consequent to the results of this study, it was concluded that inoculation of IPW improves nutritive values, phenolic compounds, antioxidant capacity, and biohydrogenation; as well as the reduction in solanine content and methane gas production. Among the microbes used in this study, A. oryzae is highly recommended because it recorded the highest content of stearic acid via the biohydrogenation process, and it reduced methane gas production than the control and IPW inoculated with L. plantarum and S. cerevisiae.